The Influence of Participatory Leadership, Quality Culture, and Job Satisfaction on Lecturer Organizational Commitment (Case Study of Universities in Indonesia) - Suryadi Damanik; Benyamin Situmorang; Rosmala Dewi (Budapest International Research and Critics University, 2021)
This study aims to determine the effect of participatory leadership on lecturers' organizational commitment, the influence of quality culture on lecturer organizational commitment, the effect of job satisfaction on lecturers' organizational commitment, the influence of participatory leadership and quality culture on job satisfaction and the commitment of lecturers' organizations at the State University of Medan, Indonesia. The sample is 202 lecturers. The instrument used a questionnaire, the data were analyzed using Path Analysis. The results of the study found that there was a significant influence of participatory leadership variables on job satisfaction. Quality culture has a positive effect on job satisfaction. Participatory leadership has a positive effect on organizational commitment. Quality culture has a positive effect on organizational commitment and job satisfaction also has a positive effect on organizational commitment. Taken together, participatory leadership, quality culture and job satisfaction have a positive effect on organizational commitment.